Evaluación de ivermectina y fenbendazol, en el control de endoparásitos en caballos del Fuerte Militar “Miguel Iturralde” de la ciudad de Loja - León Macas, Carlos Alejandro (2020)
The effect of both anthelmintic (ivermectin and fenbendazole) was evaluated, for the control of equine endoparasites at the Miguel Iturralde fort in Loja city; there were made three animal groups to check the effect, in each group there were established 36 animals with different age (12 in each group). The age groups were formed with: horses under the 5 years, horses from 6 to 10 years and horses over 10 years old. The treatments proposed were the ivermectin at 1% dosed for 2 g/100 kg of liveweight, fenbendazole at 10% dosed for 1,5 ml/20 kg of liveweight; and the witness group. The parasitosis diagnostic was made in a private laboratory in Loja city, by the use of sedimentation and floatation techniques, reporting the parasitosis in feces with eggs/gram. The weight of the animals was taken with a bovinometric tape and the dewormers application was made orally, in two applications after 16 days from the first. It was made an experimental design of random blocks with three treatments and tree blocks or repetitions where each age group were constituted in one block. Accord the results, it was established that the ivermectin was more effective than fenbendazole, in endoparasites helminths control, with a significative level of p > 0,05, while in the age groups didn´t report statistical difference in the number of eggs/gram of feces. Accordingly, it concludes that the ivermectin is very useful for the helminthiasis control (nematodes) in equine, because the next coproparasitic exam after the second application the eggs of helminths weren´t found in fecal samples, unlike the group that received fenbendazole and the witness group. Key words: Age groups, helminthiasis, coproparasitic, anthelmintic